Doppler ultrasonographic assessment of maternal and fetal arteries during normal feline gestation - Blanco, Paula Graciela (2014)
The aim of this study was to describe Doppler parameters of uterine, umbilical, fetal abdominal aorta, fetal renal and fetal internal carotid arteries, as well as fetal heart rate (FHR), during normal feline gestation. Fifteen, 1–4 years of age, weighing 2.5–3.9 kg, domestic short-hair pregnant queens, which were born in our institutional cat colony were included in this study. Color and pulsed-wave Doppler evaluations of uterine arteries were performed every 10 days (Day 0, 10, 20, 30, 40, 50, 60) from mating. Fetal Doppler and M-mode ultrasonography were performed to assess umbilical, fetal abdominal aorta, fetal renal, fetal internal carotid arteries and FHR. Both peak systolic velocity (PSV) and end diastolic velocity (EDV) of uterine artery increased up to parturition (P < 0.01), while resistance index (RI) decreased from Day 10 onwards (P < 0.01). From Day 40 onwards, RI of umbilical artery diminished, while PSV and EDV augmented (P < 0.01). Fetal abdominal aorta (P < 0.01), renal (P < 0.01) and internal carotid (P < 0.01) arteries diminished their RI from Days 40, 60 and 40 onwards, respectively. Both PSV and EDV of these three arteries increased progressively. Fetal heart rate was first registered on Day 20 when it began to increase up to Day 40 and then diminished to the end of gestation (P < 0.01). It is concluded that blood flow of uterine, umbilical, fetal abdominal aorta, fetal renal and fetal internal carotid arteries progressively increased during normal feline pregnancy, while FHR rose to mid gestation and then decreased up to parturition.